Enhanced SF6 recovery by hierarchically structured MFI zeolite - Chuah, Chong Yang (2020)
A hierarchical zeolite MFI has been synthesised and investigated for its potential feasibility in SF6/N2 separation. Zeolite MFI possessing a hierarchical microporous–mesoporous structure (MFI-2) displayed an enhanced SF6/N2 selectivity at 40 °C as compared to bulk MFI (MFI-1). More importantly, at both 25 and 40 °C, drastically improved SF6 adsorption kinetics were observed for MFI-2, owing to the presence of mesopores that can facilitate the transport of SF6 within the sorbent. Such improved adsorption kinetics allows a rapid adsorption–desorption cycling in an industrial process, which was proven by the breakthrough analysis. Furthermore, MFI-2 was found to have a much lower isosteric heat of adsorption than MFI-1, indicating its feasibility in the industrial operation as it does not require a large energy penalty for regeneration. Further evaluation with an idealised vacuum swing adsorption (VSA) model revealed that MFI-2 can exhibit more competitive performance at 40 °C than at room temperature.